2018
DOI: 10.1093/hmg/ddy396
|View full text |Cite
|
Sign up to set email alerts
|

Association of prolactin receptor (PRLR) variants with prolactinomas

Abstract: Prolactinomas are the most frequent type of pituitary tumors, which represent 10–20% of all intracranial neoplasms in humans. Prolactinomas develop in mice lacking the prolactin receptor (PRLR), which is a member of the cytokine receptor superfamily that signals via Janus kinase-2-signal transducer and activator of transcription-5 (JAK2-STAT5) or phosphoinositide 3-kinase-Akt (PI3K-Akt) pathways to mediate changes in transcription, differentiation and proliferation. To elucidate the role of the PRL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 56 publications
7
40
0
1
Order By: Relevance
“…Bromocriptine resistance has been commonly reported to accompany decreased levels of D2R 4 - 6 , 23 , 28 , 29 . Moreover, antagonizing estrogen and dopamine can regulate the endocrine functions of the other, and estrogen may decrease D2R expression or attenuate functional coupling with its downstream effector 17 , 30 , 31 . Based on these findings, D2R was also investigated in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bromocriptine resistance has been commonly reported to accompany decreased levels of D2R 4 - 6 , 23 , 28 , 29 . Moreover, antagonizing estrogen and dopamine can regulate the endocrine functions of the other, and estrogen may decrease D2R expression or attenuate functional coupling with its downstream effector 17 , 30 , 31 . Based on these findings, D2R was also investigated in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the synergistic effects of fulvestrant and bromocriptine on downstream signaling molecules, ERα- and bromocriptine-induced signaling was observed in MMQ cells treated with bromocriptine and fulvestrant alone or in combination. Key downstream markers of ERα- or bromocriptine-induced signaling, such as p38, AKT, ERK, JNK and cyclin D1 9 , 17 , 30 , 42 - 44 , were investigated by western blotting following co-culture with bromocriptine (25 μM) and fulvestrant (20 nM) for 72 h. Enhanced pJNK1/2, pERK1/2 and p38, but decreased cyclin D1 expression was observed in the combination group, while pAKT was not obviously altered (Fig. 7 D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-proliferative responses to the inhibition of the mammalian target of rapamycin (mTOR) pathway have been reported in in vitro studies with aggressive pituitary tumors [106]. Particularly for prolactinomas, Gorvin et al showed that certain variants of the prolactin receptor, like the Asn492Ile one, are associated with increased signaling by this pathway and cellular proliferation, and that everolimus was antagonizing these effects [107]. A case report described a patient with a DA-resistant prolactinoma that underwent multiple surgical resections and radiotherapy 6 years before a trial of everolimus (10 mg/ day) was attempted [108].…”
Section: Inhibitors Of Mammalian Target Of Rapamycin (Mtor)mentioning
confidence: 99%
“…kinase-2 (JAK2)/signal transducer and activator of transcription 5A (STAT5) pathway (8). Thus, the JAK2/STAT5 pathway may contribute to drug resistance in prolactinomas.…”
Section: Pimozide Augments Bromocriptine Lethality In Prolactinoma Cementioning
confidence: 99%